Studies on Schismatoglottideae (Araceae) of Borneo XXXIV – The Fruits of Schottariella mirifica - Boyce, P.C; Wong, S.Y (Aroideana, 2014)
The fruits of Schottariella mirifica P.C. Boyce & S.Y. Wong are described and illustrated for the first time and shown to be dehiscent berries, the second recorded example of this fruit type for tribe Schismatoglottideae, and the third for the family Araceae. The berries of Schottariella mirifica dehisce basally with the shed portion of the berry containing 3–5 comparatively large seeds, each fully enclosed in a fleshy white aril.